High velocity outflows along the axis of pulsed power driven rod z-pinches - Yanuka,D; Theocharous,S; Chittenden,JP; Bland,SN (AIP Advances, 2020)
We report on initial observations of high velocity outflows from the ends of a rod compressed using pulsed power. 1 mm and 2 mm diameter copper rods were placed in a water bath and driven by ∼0.6 MA currents with rise times of ∼700 ns. Laser backlit framing images and streak photography showed an outflow of the material from the ends of each rod, of the initial velocity of up to 7 km/s, which began ∼500 ns after the start of the current pulse and continued throughout the experiment. Ballistics gel was used to help separate low density gas/plasma from any solid/liquid component in the outflow, successfully capturing the material from larger diameter rods (enabling an estimate of its energy) and tracing the path of the material that passed straight through the gel with smaller rods. Experimental results were compared to 1D and 2D MHD simulations performed with the Gorgon code. These suggested that the outflow had two different components, resulting from two different physical processes. Differences in the resistivity between the copper rod and stainless steel anode result in the opening of a small gap between them and ablated stainless steel being projected above the rod, which is captured in framing and streak images. Later in time, a dense copper material, pinched by the magnetic pressure, is launched—explaining the ballistics gel results. The simulations also suggest that the tamped explosion of the rod surface plays a small role in any outflow.